Responsive Neurostimulation System (RNS) in setting of cranioplasty and history of multiple craniotomies - Jason Ledesma; Lilit Mnatsakanyan; Jack J. Lin; Indranil Sen-Gupta; Mona Sazgar; Frank P.K. Hsu; Sumeet Vadera (Interdisciplinary Neurosurgery, 2016)
Introduction: Stereoelectroencephalography (SEEG) and subdural grids (SDG) are both effective options for localizing the ictal onset zone in patients with frequent seizures. The choice of intracranial monitoring technique utilized depends upon several factors, including the patient's clinical presentation and history. This article addresses a rare instance in which SEEG was not an option due to patient's morphology. Case report A 36-year-old man with history of medically intractable epilepsy and multiple craniotomies complicated by infection and subsequent cranioplasty was presented for possible surgical evaluation. Initially, SEEG was attempted but ultimately terminated because of difficulty related to prior cranioplasty and scarring to the brain. Eventually, a subdural grid system was placed to establish the patient's ictal onset zones after which RNS implantation was performed. Discussion: The SDG placement was successful and localized the patient's ictal onset to the hand-motor region of the left hemisphere. RNS was then implanted and postoperatively the patient had a significant decrease in his seizure burden. Conclusion: The case illustrates a possible limitation of SEEG placement, particularly in patients with a history of cranioplasty and multiple prior craniotomies. We also describe the first placement of an RNS generator and system in the setting of prior cranioplasty.